Відображення світової містичної традиції у працях Володимира Соловйова (концепція Абсолюту у працях Новаліса та Соловйова) - Корнєєва, Х. (Літературознавчі обрії. Праці молодих учених, 2010)
The problem of the Absolute and world unity is the basic idea in the history of world philosophy and culture. It’s closely connected with the conception of the synthesis of science, religion and art. This conception was advanced by the representatives of the German romantic school. The German romantic philosophy had an influence upon Solovyov’s theory of world unity and also had an impact on the artistic explorations of Russian symbolists.